Implementasi Teknologi Biometrik Pada Mobile Banking Bank Syariah Indonesia (Studi kasus pada Bank Syariah Indonesia KC Bengkulu S Parman 1) - Putriana, Anggita (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This research aims to determine the implementation of biometric technology in Mobile Banking at Bank Syariah Indonesia (case study at Bank Syariah Indonesia KC Bengkulu S Parman 1), as well as to find out what are the benefits of mobile banking in implementing biometric technology. This research uses a qualitative descriptive method, the data sources are primary and secondary data. Data collection techniques include observation, interviews and documentation. The research results show that this research applies biometric technology, especially the use of fingerprints, in the BSI Mobile Bank Syariah Indonesia application. Findings show that this technology increases transaction security and user convenience by reducing the risk of identity theft and fraud and enabling fast and easy access without the need for complex passwords. As well as the benefits of mobile banking with biometric technology at Bank Syariah Indonesia. Fingerprint integration in authentication increases transaction security, ensures fast access, and protects user data. BSI Bank provides education about transaction security. These findings show that the application of biometric technology strengthens user security and comfort in digital banking services, confirming BSI's commitment to innovation and customer satisfaction.